(untitled) (Acta Scientiarum. Agronomy, 2019)
An uneven distribution of maize plants at the sowing row can decrease grain yield. This work was carried out to evaluate the effect of an increasing nitrogen rate on maize agronomic performance under different variation coefficients of plant spatial distributions at the sowing row. The experiment was conducted in Lages, Santa Catarina State, South Brazil. Three variation coefficients (VC) of plant spatial distribution (0, 50, and 100%) were tested. At the 0 level, seeds were evenly distributed 17 cm from each other. In the other treatments with uneven spatial distributions, the distances between two neighbouring seeds ranged from 2 to 54 cm. Four nitrogen side-dress rates (0, 125, 250, and 375 kgN ha-1) were evaluated. The increase in VC of plant spatial distribution decreased the leaf area and the relative chlorophyll content of the index leaf at silking, regardless of the nitrogen rate. When the variation coefficient of seed placement was enhanced from 0 to 100%, such behaviour contributed to a decrease in the number of kernels per ear and the grain yield. Therefore, increasing the amount of N was not an efficient strategy for preventing yield losses caused by irregular plant spatial distribution at the sowing row.